Los tratados de libre comercio firmados con Estados Unidos China y la Unión Europea y su relación con la balanza comercial del Perú 2007 – 2021 - Gonzales Utia, Kenny Marden (2024)
This research has thoroughly examined Peru's trade balance and the impact of Free Trade Agreements (FTAs) on its economy. Peru has experienced significant economic growth in recent decades, in part thanks to its active participation in FTAs with various countries and economic blocs. However, this growth has not been without challenges, highlighting the country's dependence on specific sectors such as mining and agriculture. The Peruvian trade balance has shown a positive trend, but the need to diversify the economy and improve the competitiveness of Peruvian products in international markets has been identified. Recommendations to achieve these goals include strengthening small and medium-sized businesses, promoting innovation and technology, and improving logistics and transportation infrastructure. In addition, it is suggested to carry out a constant analysis of FTAs to ensure that the benefits are maximized and distributed equitably. By implementing these strategies, Peru is expected to not only improve its trade position, but also foster sustainable and inclusive economic development, benefiting the entire Peruvian society.